New Findings on the Survival of Durusdinium glynnii Under Different Acclimation Methods to Low Salinities - Barbara de Cassia S. Brandão; Jéssika L. de Abreu; Deyvid Willame S. Oliveira; Clarissa Vilela F. da Silva Campos; Ingrid M. Thó de Aguiar; Pedro R. de Sena; Alfredo O. Gálvez; Carlos Yure B. Oliveira (Microorganisms)
This study investigated the effects of salinity on the growth and cell morphotype of the coral-associated dinoflagellate Durusdinium glynnii under two acclimation strategies: abrupt saline shock (S5) and gradual reduction (S2). Results revealed optimal growth rates (µ = 0.22–0.35 day−1) at salinities of 20–30 g L−1, while extreme conditions (10 and 40 g L−1) significantly inhibited development. The S2 strategy enabled adaptation to salinities as low as 16 g L−1, maintaining higher cell densities compared to the S5 method. Gradual salinity reduction also influenced cellular morphology: below 12 g L−1, a predominant shift occurred from motile forms (mastigotes) to non-motile spherical structures (coccoid), suggesting an adaptive response to osmotic stress, gradually reducing the growth rate due to the lower reproductive rate of coccoid cells, as previously reported in studies. The findings conclude that D. glynnii is a euryhaline species, tolerant of moderate salinity variations (16–30 g L−1) but limited under extreme conditions. Its morphological plasticity and gradual acclimation capacity highlight its potential for cultivation in brackish environments and biomass production for biotechnological applications, such as antioxidants and antimicrobials. The data provide a foundation for future studies on molecular mechanisms of salinity tolerance, essential for coral conservation strategies and bioprospecting efforts.